Kebijakan Dana Desa di Kecamatan Malangke Kabupaten Luwu Utara Perspektif Al Maslahah Al Mursalah - Mansur, Mansur; Nur, Muhammad Tahmid; Fasiha, Fasiha; Darwis, M Ihsan (Universitas Cokroaminoto Yogyakarta, 2024)
The aim of the research is to find out the Village Fund Policy Regulations, to find out the Village Fund policy in Malangke District, North Luwu Regency, al-maslahah al-mursalah perspective. Research results show that in general the village government uses Village Funds wisely in accordance with binding regulations or rules, such as building village roads, building clean water facilities, community economic empowerment programs, building sports facilities and providing educational facilities and infrastructure and educational scholarship programs. So there is often a conflict of views between the government and village communities, because a solution is needed to avoid existing conflicts. Through the concept of maslahah al-mursalah, village policy makers and stakeholders can use Village Funds to build public facilities. The use of these funds can be justified on the grounds of achieving public benefit and improving the quality of life of village communities. One of the problems found in allocating Village Funds is the difference between community needs and the use of Village Funds by the village government